Cosmic archeology with the Cosmic Microwave Background Radiation - Souza, Carlos Alexandre Wuensche de (2010)
Cosmology is a relatively new science, and requests a permanent flow of observations to support theoretical predictions from scientists working in the field. The Cosmic Microwave Background Radiation (CMBR) is one of the observables used to give this support being the most ancient electromagnetic signal we can detect, the oldest direct source from the early Universe and a solid evidence that the Big Bang model is the best available description of our Universe. From CMBR measured properties - temperature, angular distribution and polarization - we can extract information about the characteristics of the early Universe. From them, much as an archaeologist collecting fossils and relics can unveil past images based upon present knowledge, cosmologists study the properties of the CMBR as a Big Bang fossil trying to understandhow the Universe "started" and evolved to what we see today. We will discuss in this article some challenges faced by modern cosmology to be able to describe our Universe and how CMBR observations can help in this task.